ANALISIS PRINSIP-PRINSIP PERLINDUNGAN HAK ASASI MANUSIA TERHADAP ANAK BINAAN PADA LEMBAGA PEMBINAAN KHUSUS ANAK (LPKA) KELAS II PALU - Verra Veronika (TADULAKO MASTER LAW JOURNAL, 2025)
This study aims to determine and analyze the application of the principles of human rights protection to fostered children at the Class II Palu Special Children'S Development Institution and the inhibiting factors in fostering children at the Class II Palu Special Children'S Development Institution, with empirical legal research. The results of the research LPKA Class II Palu has applied the principles of human rights protection in the development of fostered children, in line with the Minimum Standard Rules issued by the United Nations on the Administration of Juvenile Justice (Beijing Rules).  The implementation of human rights principles has been implemented with the fulfillment of children's rights as in the Universal Declaration of Human Rights (UDHR) that all people are equal before the law and are entitled to equal protection of the law without discrimination, including children in the guidance of LPKA for committing criminal acts. LPKA Class II Palu, has implemented the Convention on the Rights of the Child (KHA), the implementation of the process of implementing the protection of children based on the principles of non discrimination, the best interests of the child, prioritizing the child's right to life, respecting the views of the child. And the inhibiting factors in the development of children in LPKA Class II Palu are Human Resources, Different Backgrounds of Fostered Children, Facilities and Infrastructure, Budget Limitations and Society. Penelitian ini bertujuan untuk mengetahui dan menganalisis penerapan prinsip-prinsip perlindungan hak asasi manusia terhadap anak binaan di Lembaga Pembinaan Khusus Anak Kelas II Palu dan faktor-faktor penghambat dalam pembinaan anak di Lembaga Pembinaan Khusus Anak Kelas II Palu, dengan jenis penelitian hukum empiris. Hasil penelitian LPKA Kelas II Palu telah menerapkan prinsip-prinsip perlindungan hak asasi manusia dalam pembinaan anak binaan, sejalan dengan Aturan Standar Minimum yang dikeluarkan oleh Perserikatan Bangsa-Bangsa tentang Administrasi Peradilan Anak (Beijing Rules).  Penerapan prinsip-prinsip HAM telah diimplementasikan dengan pemenuhan hak-hak anak sebagaimana dalam Deklarasi Universal Hak Asasi Manusia (DUHAM) bahwa semua orang sama di hadapan hukum dan berhak mendapatkan perlindungan hukum yang sama tanpa diskriminasi, termasuk anak dalam pembinaan LPKA karena melakukan tindak pidana. LPKA Kelas II Palu, telah mengimplementasikan Konvensi Hak Anak (KHA), pelaksanaan proses penyelenggaraan perlindungan anak berdasarkan prinsip non diskriminasi, kepentingan terbaik bagi anak, mengutamakan hak anak untuk hidup, menghargai pendapat anak. Dan faktor penghambat dalam pembinaan anak di LPKA Kelas II Palu adalah Sumber Daya Manusia, Latar Belakang Anak Binaan yang Berbeda, Sarana dan Prasarana, Keterbatasan Anggaran dan Masyarakat.